Aleocharine rove beetles of New Hampshire, USA: new taxa and new records (Coleoptera, Staphylinidae, Aleocharinae) - Klimaszewski, Jan; Chandler, Donald S.; Davies, Anthony; Bourdon, Caroline (Zootaxa, 2023)
Based on the specimens housed primarily in the University of New Hampshire Insect Collection (UNH) and the Canadian National Collection (CNC), we present here a comprehensive faunal review of aleocharine beetles of the state and provide new distribution and natural history data. We report 252 species from New Hampshire belonging to some 74 genera in 15 tribes; 159 of these constitute new New Hampshire state records (NSR), of which 37 (excluding new species and including 1 New York record) constitute new country distribution records (NCR) for the USA. In addition, we provide 36 new state records for ME, with 5 of these species not yet known from NH, seven new state records for MA, two new state records for PA and VT, and one each for CT, DE, MI, NC, NY (also a NCR), OH, and OK. One new genus, Belladonna Klimaszewski and Chandler is erected, and nine species are described as new to science (alphabetical order): Agaricomorpha hampshirensis Klimaszewski and Chandler, sp. n., Atheta ellisi Klimaszewski and Chandler sp. n, Atheta monroe Klimaszewski and Chandler, sp. n., Atheta struyvei Klimaszewski and Chandler sp. n, Belladonna barryi Klimaszewski and Chandler, sp. n., Belladonna fortieri Klimaszewski and Chandler, sp. n., Colusa smetanai Klimaszewski and Chandler, sp. n., Philhygra pinkhami Klimaszewski and Chandler sp. n., and P. pseudomagniceps Klimaszewski and Chandler, sp. n. Undescribed females of Aleochara daviesi Klimaszewski and Brunke, and Silusa langori Klimaszewski, are described and illustrated. Illustrations of Atheta (Tetropla) tubericauda Bernhauer are provided for the first time, based on a male from New Hampshire. A new combination is proposed for Atheta (Dimetrota) mcalpinei Klimaszewski and Webster.